Living in two worlds : the American Indian experience illustrated - Eastman, Charles A., 1858-1939 (Library of perennial philosophy. American Indian traditions series., 2010)
"Fitzgerald's work focuses on Charles Eastman's (Ohiyesa's) compelling story of embracing the traditional cultural ideals of his nomadic ancestors while living in the modern industrialized world of his time. Born in a buffalo-hide tipi in 1858, Eastman was raised as a traditional Sioux Indian in his youth, but was catapulted into the dominant white society of his time, becoming a medical doctor who cared for wounded Indians after the 1890 massacre at Wounded Knee and helping to co-found the Boy Scouts of America in 1910." This book features: selections from Charles Eastman's five most important books; more than 275 color and black & white vintage photographs, paintings, vignettes, timelines, and maps; nine interviews with contemporary American Indian leaders on their experience of "living in two worlds"; and thought-provoking discussion questions and lists of free supplementary study materials."--Jacket.